Molecular Engineering for Function‐Tailored Interface Modifier in High‐Performance Perovskite Solar Cells (Adv. Energy Mater. 27/2022). Issue 27 (21st July 2022) - Sung, Sae Jin; Im, Jino; Kim, Geunjin; Moon, Chan Su; Yoo, Jason J.; Shin, Seong Sik; Jeon, Nam Joong; Ma, Boo Soo; Kim, Dong Jun; Kim, Taek‐Soo; Seo, Jangwon
Abstract : Perovskite Solar Cells In article number 2200758, Jangwon Seo and co‐workers introduce [2‐(9 H ‐carbazol‐9‐yl)ethyl]phosphonic acid (CEPA) as an interface modifier at the interface of the perovskite and hole transporting layer (HTL) into n‐i‐p perovskite solar cells. CEPA reduces surface traps and induces molecular interactions at the interface of the CEPA‐HTL for enhanced interfacial adhesion energy and good mechanical stability, thereby improving the power conversion efficiency and the stability of poly(triarylamine) HTL‐based devices.